Wogonin Alleviates Kidney Tubular Epithelial Injury in Diabetic Nephropathy by Inhibiting PI3K/Akt/NF-κB Signaling Pathways - Lei L; Zhao J; Liu XQ; Chen J; Qi XM; Xia LL; Wu YG (Dove Medical Press, 2021)
Lei Lei,1 Jing Zhao,1 Xue-Qi Liu,1 Juan Chen,1 Xiang-Ming Qi,1 Ling-Ling Xia,2 Yong-Gui Wu1 1Department of Nephropathy, the First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People's Republic of China; 2Department of Infectious Disease, the First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People's Republic of ChinaCorrespondence: Ling-Ling XiaDepartment of Infectious Disease, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People's Republic of ChinaTel +86 0551 6292 2450Email 13966684365@163.comYong-Gui WuDepartment of Nephropathy, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People's Republic of ChinaTel +86 0551 6292 2111Email wuyonggui@medmail.com.cnIntroduction: Kidney tubular epithelial injury is one of the key factors in the progression of diabetic nephropathy (DN). Wogonin is a kind of flavonoid, which has many pharmacological effects, such as anti-inflammation, anti-oxidation and anti-fibrosis. However, the effect of wogonin in renal tubular epithelial cells during DN is still unknown.Materials and Methods: STZ-induced diabetic mice were given doses of wogonin (10, 20, and 40 mg/kg) by intragastric administration for 16 weeks. The metabolic indexes from blood and urine and pathological damage of renal tubules in mice were evaluated. Human tubular epithelial cells (HK-2) were cultured in high glucose (HG) condition containing wogonin (2μM, 4μM, 8μM) for 24 h. Tubular epithelial cell inflammation and autophagic dysfunction both in vivo and in vitro were assessed by Western blot, qRT-PCR, IHC, and IF analyses.Results: The treatment of wogonin attenuated urinary albumin and histopathological damage in tubulointerstitium of diabetic mice. We also found that wogonin down-regulated the expression of pro-inflammatory cytokines and autophagic dysfunction in vivo and in vitro. Molecular docking and Cellular Thermal Shift Assay (CETSA) results revealed that mechanistically phosphoinositide 3-kinase (PI3K) was the target of wogonin. We then found that inhibiting PI3K eliminated the protective effect of wogonin. Wogonin regulated autophagy and inflammation via targeting PI3K, the important connection point of PI3K/Akt/NF-κB signaling pathway.Conclusion: Our study is the first to demonstrate the novel role of wogonin in mitigating tubulointerstitial fibrosis and renal tubular cell injury via regulating PI3K/Akt/NF-κB signaling pathway-mediated autophagy and inflammation. Wogonin might be a latent remedial drug against tubular epithelial injury in DN by targeting PI3K.Keywords: diabetic nephropathy, tubular epithelial cell, wogonin, inflammation, autophagy, PI3K/Akt/NF-κB pathway